The Diffusion of AI-Driven Digital Da’wah Innovation In Communication Media: A Perspective of Q.S. Al-Mulk 23 And Audio-Visual Cognitive Analysis On Instagram @Ace_Timetraveller - Nadya Syahda Faradillah; Ayu Latifah; Siti Riskiyah; Rofiqotudz Dzakiyah; Moh. Ali Aziz (Universitas Islam Internasional Darullughah Wadda'wah, 2026)
The rapid evolution of Artificial Intelligence has fundamentally transformed da’wah communication on social media. This study investigates the dynamics of Artificial Intelligence-based digital da’wah on the Instagram account @ace_timetraveller through the lens of Q.S. Al-Mulk:23 and audio-visual cognitive analysis. Employing a descriptive qualitative method with observation and documentation, this research utilizes Diffusion of Innovations theory and thematic Qur’anic interpretation. Findings reveal that Artificial Intelligence enhances content production efficiency and accelerates the diffusion of religious messages among digital audiences. Audio-visual elements significantly heighten audience engagement and comprehension by optimizing cognitive processes, attention, comprehension, and retention, which are further augmented by Artificial Intelligence-driven designs. Furthermore, Q.S. Al-Mulk:23 underscores the necessity of optimizing hearing, sight, and heart as primary instruments for perceiving and internalizing da’wah. In conclusion, Artificial Intelligence -driven da’wah represents a relevant communication innovation that remains effective when anchored in Islamic theological values. The strategic integration of technology and audio-visual media is pivotal for enhancing the quality and impact of digital da’wah in the modern era.